Light high-strength electromagnetic shielding and infrared stealth composite aerogel and preparation method thereof
By combining metal ion-induced MXene cross-linking and modified aramid paper honeycombs, lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel was prepared, which solved the shortcomings of existing materials in terms of mechanical properties and processability, and achieved excellent electromagnetic shielding and infrared stealth performance.
Patent Information
- Application Number
- CN202411779492.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lightweight and efficient electromagnetic shielding and infrared stealth composite materials have shortcomings in mechanical properties and processability, and it is difficult to meet the application needs of aerospace, weapons and equipment, electronics and electrical fields.
By introducing metal ions to induced MXene cross-linking, combined with modified aramid paper honeycombs as the mechanical properties enhancement framework, a lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel was prepared by freeze-drying.
It significantly improves the mechanical properties and electromagnetic shielding performance of composite aerogels, while maintaining their lightweight characteristics, achieving excellent infrared stealth performance, and is suitable for aerospace, military engineering, electronics and electrical fields.
Smart Images

Figure CN119591928A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding and infrared stealth composite materials, and relates to a lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel. The invention also relates to a preparation method of the lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel. Background Art
[0002] With the rapid development of electronic equipment and wireless communication technology in the fields of aerospace, weapons and equipment, and electronics and electrical, information security issues caused by electromagnetic radiation interference and infrared target exposure (such as temperature changes caused by the operation of electronic equipment and aircraft engines) have become increasingly prominent, and there is an urgent need to develop lightweight and efficient electromagnetic shielding and infrared stealth materials to attenuate electromagnetic waves and protect infrared targets. Traditional metal materials such as aluminum, copper, and silver all show high electromagnetic shielding effectiveness and low infrared emissivity, but they have problems such as high density, difficult molding and high cost. Polymer-based conductive composites (CPCs) have the advantages of light weight, chemical corrosion resistance, and easy processing, but their infrared stealth performance is poor and the percolation threshold is high. To achieve ideal electromagnetic shielding effectiveness, a high amount of filler is usually required, which seriously affects its processability and mechanical properties. Therefore, it is of great significance to develop lightweight and efficient dual-function electromagnetic shielding and infrared stealth composite materials.
[0003] In recent years, conductive MXene aerogels with three-dimensional porous structures have attracted much attention in the field of lightweight electromagnetic shielding and infrared stealth composite materials. The introduction of porous structures can not only reduce the density of composite materials, but also improve the impedance matching of composite materials, effectively enhance the internal multiple reflection loss of incident electromagnetic waves, thereby improving electromagnetic wave absorption and electromagnetic shielding effectiveness. In addition, MXene has a low infrared emissivity comparable to that of metals (0.19 in the wavelength range of 7 to 14 μm), and has good application value in the field of infrared stealth materials. According to the Stefan-Boltzmann law, the infrared stealth performance can be effectively improved by reducing the infrared emissivity and / or reducing the surface temperature of the infrared target. Therefore, the synergistic effect of MXene's intrinsic low infrared emission and the efficient thermal insulation of the porous structure gives MXene aerogels excellent infrared stealth performance. Therefore, MXene aerogels have both light weight, high electromagnetic shielding effectiveness and excellent infrared stealth performance. The methods for preparing MXene aerogels mainly include freeze-drying, hydrazine hydrate induced foaming, 3D printing and sacrificial template methods. However, the MXene aerogels prepared at present generally have poor mechanical properties and are difficult to use as structural materials. In addition, gelation is difficult during the preparation process and the size shrinkage is large, which greatly limits its application in aerospace, weapons and equipment, and electronic and electrical fields.
[0004] Therefore, the development of MXene-based composite aerogels that are lightweight, high-strength, and have excellent electromagnetic shielding and infrared stealth properties has important application value in aerospace, weaponry, and electronic and electrical fields. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, by introducing metal ions to induce MXene cross-linking to improve dimensional stability, and by utilizing the characteristics of aramid paper honeycomb that is light in weight and has high strength and high stiffness to improve the mechanical properties of MXene aerogel.
[0006] Another object of the present invention is to provide a lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel.
[0007] The first technical solution adopted by the present invention is a method for preparing a lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, which specifically includes the following steps:
[0008] Step 1, prepare Ti 3 C 2 T x MXene aqueous dispersion;
[0009] Step 2, pre-treating the aramid paper honeycomb;
[0010] Step 3, preparing a polydopamine-modified aramid paper honeycomb according to the product obtained in step 2;
[0011] Step 4, preparing an aramid paper honeycomb reinforced MXene-based composite hydrogel according to the products obtained in step 1 and step 3;
[0012] Step 5, freezing the aramid paper honeycomb reinforced MXene-based composite hydrogel obtained in step 4 in liquid nitrogen, and completely drying it in a freeze dryer to obtain an aramid paper honeycomb reinforced MXene-based composite aerogel.
[0013] The present invention is also characterized in that:
[0014] The specific process of step 1 is:
[0015] The MAX phase ceramic powder was added to a hydrochloric acid / lithium fluoride mixed solution and stirred at 50 °C for 48 h to obtain a black dispersion, which was then washed, centrifuged and vibrated to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion.
[0016] In step 1, MXene is prepared in a mixed solution system of hydrochloric acid and lithium fluoride using 200-400 mesh MAX phase ceramic as raw material, and the ratio of MAX phase ceramic, lithium fluoride and hydrochloric acid is 1-2g:1-2g:20-40mL, Ti 3 C 2 T x The size of MXene flakes is 0.1 to 2 μm.
[0017] The specific process of step 2 is:
[0018] The aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a vacuum oven at 50-100° C. The aramid paper honeycomb is immersed in a 5-15 g / L NaOH solution, heated and stirred, washed with deionized water, and then dried in a vacuum oven at 70-100° C. The aramid paper honeycomb is immersed in a 33wt% hydrochloric acid solution for 1-5 minutes for ion exchange, washed with deionized water, and then dried in an oven at 100-120° C. for 5-10 hours to obtain the product.
[0019] In step 2, the aramid paper honeycomb is a para-aramid paper honeycomb or a meta-aramid paper honeycomb.
[0020] The specific process of step 3 is:
[0021] Dissolve tris(hydroxymethyl)aminomethane in deionized water, add hydrochloric acid solution, adjust the pH of the solution to alkaline, prepare Tris-HCl buffer, then add dopamine hydrochloride to the Tris-HCl buffer, ultrasonically treat, stir until the solution turns pink, add the aramid paper honeycomb obtained in step 2, and react at room temperature for 5 to 24 hours to obtain a polydopamine-modified aramid paper honeycomb.
[0022] The specific process of step 4 is:
[0023] The Ti prepared in step 1 3 C 2 T x The MXene aqueous dispersion is poured into the mold, and then the metal ion solution is added and mechanically stirred until uniform. The modified aramid paper honeycomb is completely immersed and gelled at room temperature for 5 to 15 minutes to obtain the aramid paper honeycomb reinforced MXene-based composite hydrogel.
[0024] Step 4 Ti 3 C 2 T x The concentration of MXene aqueous dispersion is 8-16 mg / mL;
[0025] In step 4, the metal ion is Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Mg 2+ and Ca 2+ One of them.
[0026] The concentration of the metal ion solution in step 4 is 0.6-1.0M.
[0027] In step 5, the freezing time in liquid nitrogen is 5 to 10 minutes; the freeze-drying time is 72 to 150 hours.
[0028] The second technical solution adopted by the present invention is that the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel is prepared by adopting the preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel.
[0029] The beneficial effect of the present invention is that the present invention uses high-performance modified aramid paper honeycomb as a reinforcement skeleton, and develops a lightweight and high-strength aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel through metal ion-induced gelation and freeze-drying strategies. 2+ The introduction of metal cations can induce Ti 3 C 2 T x The gelation of MXene aqueous dispersion improves the structural stability of the composite aerogel structure and overcomes the 3 C 2 T x MXene is difficult to form a stable three-dimensional porous aerogel. The stable porous structure formed is conducive to enhancing the interface multiple reflection and scattering of electromagnetic waves, thereby improving the electromagnetic wave absorption loss and the overall electromagnetic shielding effectiveness. The polydopamine modification of aramid paper honeycomb improves its adhesion to Ti 3 C 2 T x In addition, metal cations can also improve the interfacial interaction between modified aramid paper honeycomb and Ti through coordination chemistry. 3 C 2 T x The interaction between MXenes improves the structural performance stability of the composite aerogel. Therefore, the introduction of modified aramid paper honeycomb significantly improves the mechanical properties of the composite aerogel while maintaining its lightweight characteristics. Thanks to the multiple reflection and scattering losses at the porous structure interface, the conductive network conductive loss, and the Ti 3 C 2 T x The synergistic effect of MXene dipole and interface polarization loss, the resulting composite aerogel has excellent electromagnetic shielding performance. Moreover, the porous structure is highly efficient in thermal insulation and Ti 3 C 2 T xThe synergistic effect of MXene's low infrared emission gives the composite aerogel excellent infrared stealth performance. The preparation method adopted by the present invention is simple, efficient, green and environmentally friendly, has strong controllability in operation, is low in cost, and is easy to industrialize. The presence of aramid paper honeycomb and MXene porous structure makes the prepared conductive composite aerogel material have the characteristics of light weight, high strength, high electromagnetic shielding effectiveness and infrared stealth. Therefore, the aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel prepared by the present invention has good application prospects in the fields of aerospace, military engineering, and electronics and electrical engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the modified aramid paper honeycomb reinforced MXene-based composite aerogel obtained in Example 5 of the method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel of the present invention;
[0031] Figure 2 This is a scanning electron microscope photograph of the modified para-aramid paper honeycomb reinforced MXene-based composite aerogel obtained in Example 5 of the method for preparing a lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel of the present invention;
[0032] Figure 3 This is the compressive stress-strain curve of the unreinforced MXene aerogel obtained in Comparative Example 1 of the method for preparing the lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel of the present invention;
[0033] Figure 4 This is the compressive stress-strain curve of the modified para-aramid paper honeycomb reinforced MXene-based composite aerogel obtained in implementation 5 of the method for preparing the lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel of the present invention. DETAILED DESCRIPTION
[0034] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0035] The light-weight, high-strength electromagnetic shielding and infrared stealth composite aerogel of the present invention comprises Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel Ti obtained by metal ion-induced gelation-freeze drying 3 C 2 T x MXene aerogel is a three-dimensional porous conductive network with modified aramid paper honeycomb as the mechanical performance enhancement skeleton; the metal ions in the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel are Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Mg2+ and Ca 2+ One of the 3 C 2 T x MXene is prepared from 200-400 mesh MAX phase ceramics in a mixed solution of hydrochloric acid and lithium fluoride, with a sheet size of 0.1-2 μm; Ti 3 C 2 T x The mass ratio of MXene to metal ions is 100:2-10; the aramid paper honeycomb is a para-aramid paper honeycomb or a meta-aramid paper honeycomb; the mass density of the aramid paper honeycomb is 32-128 kg / m 3 ; The modified aramid paper honeycomb is used as a mechanical performance enhancement skeleton, which effectively improves the pressure-bearing performance of the composite aerogel.
[0036] The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel of the present invention specifically comprises the following steps:
[0037] Step 1: Add MAX phase ceramic powder to a hydrochloric acid / lithium fluoride mixed solution and stir at 50°C for 48 hours to obtain a black dispersion, which is then washed, centrifuged and vibrated to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion;
[0038] In step 1, MXene is prepared in a mixed solution system of hydrochloric acid and lithium fluoride using 200-400 mesh MAX phase ceramics as raw materials, and the ratio of MAX phase ceramics, lithium fluoride and hydrochloric acid is 1-2g:1-2g:20-40mL, Ti 3 C 2 T x The size of MXene flakes is 0.1 to 2 μm.
[0039] Step 2, ultrasonically clean the aramid paper honeycomb in anhydrous ethanol and then wash it with deionized water, and then dry it in a vacuum oven at 50-100°C. Immerse the aramid paper honeycomb in a 5-15g / L NaOH solution, heat it to 60°C, stir it for 2.5h, wash it with deionized water, and then dry it in a vacuum oven at 70-100°C. Soak the aramid paper honeycomb in a 33wt% hydrochloric acid solution for 1-5min for ion exchange, wash it with deionized water, and then dry it;
[0040] The aramid paper honeycomb in step 2 is a para-aramid paper honeycomb or a meta-aramid paper honeycomb. The mass density of the aramid paper honeycomb is 32 to 128 kg / m 3 .
[0041] Step 3, dissolving tris(hydroxymethyl)aminomethane in deionized water, adding hydrochloric acid solution, adjusting the solution pH to 8.5, and preparing Tris-HCl buffer. Then, adding 150 mg of dopamine hydrochloride into 150 mL of Tris-HCl buffer, ultrasonically treating for 5 min, stirring until the solution turns pink, adding the aramid paper honeycomb obtained in step 2, and reacting at room temperature for 5 to 24 h to prepare polydopamine modified aramid paper honeycomb;
[0042] Step 4: Ti obtained in step 1 3 C 2 T x The MXene aqueous dispersion is poured into the mold, and then the metal ion solution is added and mechanically stirred until uniform, and the modified aramid paper honeycomb of appropriate size is completely immersed, and gelation is carried out at room temperature for 5 to 15 minutes to obtain the aramid paper honeycomb reinforced MXene-based composite hydrogel;
[0043] In step 4, Ti 3 C 2 T x The concentration of MXene aqueous dispersion is 8-16 mg / mL.
[0044] The metal ion in step 4 can be Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Mg 2+ and Ca 2+ One of them.
[0045] The concentration of the metal ion solution in step 4 is 0.6-1.0M.
[0046] Step 5, the aramid paper honeycomb reinforced MXene-based composite hydrogel obtained in step 4 is placed in liquid nitrogen for 5 to 10 minutes, and further placed in a freeze dryer for complete drying to obtain an aramid paper honeycomb reinforced MXene-based composite aerogel. The freeze drying time in step 5 is 72 to 150 hours.
[0047] Example 1
[0048] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene sheets is 0.1 μm; the metal ions are Ca 2+ ; Aramid paper honeycomb is para-aramid paper honeycomb with a mass density of 32kg / m 3 ; The Ti 3C 2 T x MXene and Ca 2+ A three-dimensional porous conductive aerogel is constructed; the modified para-aramid paper honeycomb is used as a mechanical performance enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 72 hours.
[0049] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 200 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1g:1g:20mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of the MXene layer is 0.1 to 2 μm; the aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a 70°C vacuum oven. The para-aramid paper honeycomb is immersed in a 5g / L NaOH solution, heated to 60°C, stirred for 2.5h, washed with deionized water and dried in a vacuum oven at 80°C. The aramid paper honeycomb is soaked in a 33wt% hydrochloric acid solution for 1min for ion exchange, washed with deionized water and dried; tris(hydroxymethyl)aminomethane is dissolved in deionized water, hydrochloric acid solution is added, the pH of the solution is adjusted to 8.5, and Tris-HCl buffer is prepared. Then, 150mg of dopamine hydrochloride is added to 150mL Tris-HCl buffer, ultrasonically treated for 5min, stirred until the solution turns pink, added to the aramid paper honeycomb, and reacted at room temperature for 5h to prepare polydopamine-modified aramid paper honeycomb; Ti with a concentration of 8mg / mL is added. 3 C 2 T x The MXene aqueous dispersion was poured into the mold, and then Ca2PO4 with a concentration of 0.6 M was added. 2+ The aqueous solution was mechanically stirred until uniform, and the modified aramid paper honeycomb was completely immersed in it, and gelled at room temperature for 5 minutes to obtain the aramid paper honeycomb reinforced Ca 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Ca 2+ -MXene composite hydrogel was frozen in liquid nitrogen for 5 min and further placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Ca 2+ -MXene composite aerogel. The mass density of the obtained aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 39.1kg / m 3The compression strength is 1.18MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 41.2dB, and the radiation temperature of a 100℃ infrared target can be reduced to 39.2℃.
[0050] Example 2
[0051] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene flakes is 1 μm; the metal ion is Zn 2+ ; Aramid paper honeycomb is meta-aramid paper honeycomb with a mass density of 32kg / m 3 ;Ti 3 C 2 T x MXene and Zn 2+ A three-dimensional porous conductive aerogel is constructed; the modified meta-aramid paper honeycomb is used as a mechanical performance enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 96 hours.
[0052] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 300 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1g:2g:30mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of the MXene layer is 2μm; the aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a 70°C vacuum oven. The meta-aramid paper honeycomb is immersed in a 10g / L NaOH solution, heated to 60°C, stirred for 2.5h, washed with deionized water and dried in a vacuum oven at 80°C. The aramid paper honeycomb is soaked in a 33wt% hydrochloric acid solution for 2min for ion exchange, washed with deionized water and dried; tris(hydroxymethyl)aminomethane is dissolved in deionized water, hydrochloric acid solution is added, the pH of the solution is adjusted to 8.5, and Tris-HCl buffer is prepared. Then, 150mg of dopamine hydrochloride is added to 150mL Tris-HCl buffer, ultrasonically treated for 5min, stirred until the solution turns pink, added to the aramid paper honeycomb, and reacted at room temperature for 10h to prepare polydopamine-modified aramid paper honeycomb; Ti with a concentration of 10mg / mL3 C 2 T x MXene aqueous dispersion is poured into the mold, and Zn with a concentration of 0.7 M is added 2+ The aqueous solution was mechanically stirred until uniform, and the modified aramid paper honeycomb was completely immersed in it. The aramid paper honeycomb was gelled at room temperature for 10 minutes to obtain the aramid paper honeycomb reinforced Zn 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Zn 2+ -MXene composite hydrogel was frozen in liquid nitrogen for 5 min and then placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Zn 2+ -MXene composite aerogel. The mass density of the obtained aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 40.5kg / m 3 The compression strength is 0.95MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 50.6dB, and the radiation temperature of a 100℃ infrared target can be reduced to 38.8℃.
[0053] Example 3
[0054] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene flakes is 2 μm; the metal ions in the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel are Cu 2+ ; Aramid paper honeycomb is para-aramid paper honeycomb with a mass density of 128kg / m 3 ;Ti 3 C 2 T x MXene and Cu 2+ A three-dimensional porous conductive aerogel is constructed; the modified para-aramid paper honeycomb is used as a mechanical performance enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 120 hours.
[0055] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 400 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 2g:1g:40mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 Tx The size of the MXene layer is 2μm; the aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a 70°C vacuum oven. The para-aramid paper honeycomb is immersed in a 15g / L NaOH solution, heated to 60°C, stirred for 2.5h, washed with deionized water and dried in a vacuum oven at 80°C. The aramid paper honeycomb is soaked in a 33wt% hydrochloric acid solution for 5min for ion exchange, washed with deionized water and dried; tris(hydroxymethyl)aminomethane is dissolved in deionized water, hydrochloric acid solution is added, the pH of the solution is adjusted to 8.5, and Tris-HCl buffer is prepared. Then, 150mg of dopamine hydrochloride is added to 150mL Tris-HCl buffer, ultrasonically treated for 5min, stirred until the solution turns pink, added to the aramid paper honeycomb, and reacted at room temperature for 15h to prepare polydopamine-modified aramid paper honeycomb; Ti with a concentration of 12mg / mL is added. 3 C 2 T x The MXene aqueous dispersion was poured into the mold, and then Cu with a concentration of 0.8 M was added. 2+ The aqueous solution was mechanically stirred until uniform, and the modified aramid paper honeycomb was completely immersed in it. The aramid paper honeycomb was gelled at room temperature for 15 minutes to obtain the aramid paper honeycomb reinforced Cu 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Cu 2+ -MXene composite hydrogel was frozen in liquid nitrogen for 10 min and further placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Cu 2+ -MXene composite aerogel. The mass density of the obtained aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 138.6kg / m 3 , the compression strength is 5.48MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 62.3dB, and the radiation temperature of a 100℃ infrared target can be reduced to 38.0℃.
[0056] Example 4
[0057] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene flakes is 2 μm; the metal ions in the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel are Ni 2+ ; Aramid paper honeycomb is meta-aramid paper honeycomb with a mass density of 48kg / m 3 ;Ti 3 C 2T x MXene and Ni 2+ A three-dimensional porous conductive aerogel is constructed; the modified meta-aramid paper honeycomb is used as a mechanical property enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 150 hours.
[0058] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 400 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1g:2g:30mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of the MXene layer is 0.1 to 2 μm; the aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a 70°C vacuum oven. The aramid paper honeycomb is immersed in a 10g / L NaOH solution, heated to 60°C, stirred for 2.5h, washed with deionized water and dried in a vacuum oven at 80°C. The meta-aramid paper honeycomb is soaked in a 33wt% hydrochloric acid solution for 1min for ion exchange, washed with deionized water and dried; tris(hydroxymethyl)aminomethane is dissolved in deionized water, hydrochloric acid solution is added, the pH of the solution is adjusted to 8.5, and Tris-HCl buffer is prepared. Then, 150mg of dopamine hydrochloride is added to 150mL Tris-HCl buffer, ultrasonically treated for 5min, stirred until the solution turns pink, added to the aramid paper honeycomb, and reacted at room temperature for 24h to prepare polydopamine-modified aramid paper honeycomb; Ti with a concentration of 14mg / mL 3 C 2 T x The MXene aqueous dispersion was poured into the mold, and Ni with a concentration of 0.9 M was added. 2+ The aqueous solution was mechanically stirred until uniform, and the modified aramid paper honeycomb was completely immersed in it. The aramid paper honeycomb was gelled at room temperature for 5 minutes to obtain the aramid paper honeycomb reinforced Ni 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Ni 2 + -MXene composite hydrogel was frozen in liquid nitrogen for 10 min and further placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Ni 2+ -MXene composite aerogel. The mass density of the obtained aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 59.4kg / m 3, the compression strength is 1.92MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 71.7dB, and the radiation temperature of a 100℃ infrared target can be reduced to 37.4℃.
[0059] Example 5
[0060] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene sheets is 0.1 μm; the metal ions are Co 2+ ; Aramid paper honeycomb is para-aramid paper honeycomb with a mass density of 48kg / m 3 ;Ti 3 C 2 T x MXene and Co 2+ A three-dimensional porous conductive aerogel is constructed; the modified para-aramid paper honeycomb is used as a mechanical performance enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 72 hours.
[0061] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 200 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1g:1g:20mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of the MXene layer is 0.1 to 2 μm; the aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a 70°C vacuum oven. The aramid paper honeycomb is immersed in a 10g / L NaOH solution, heated to 60°C, stirred for 2.5h, washed with deionized water and dried in a vacuum oven at 80°C. The para-aramid paper honeycomb is soaked in a 33wt% hydrochloric acid solution for 1min for ion exchange, washed with deionized water and dried; tris(hydroxymethyl)aminomethane is dissolved in deionized water, hydrochloric acid solution is added, the pH of the solution is adjusted to 8.5, and Tris-HCl buffer is prepared. Then, 150mg of dopamine hydrochloride is added to 150mL Tris-HCl buffer, ultrasonically treated for 5min, stirred until the solution turns pink, added to the aramid paper honeycomb, and reacted at room temperature for 24h to prepare polydopamine-modified aramid paper honeycomb; Ti with a concentration of 16mg / mL is added.3 C 2 T x The MXene aqueous dispersion was poured into the mold, and then Co with a concentration of 1.0 M was added. 2+ The aqueous solution was mechanically stirred until uniform, and the modified aramid paper honeycomb was completely immersed in it. The aramid paper honeycomb was gelled at room temperature for 5 minutes to obtain the aramid paper honeycomb reinforced Co 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Co 2 + -MXene composite hydrogel was frozen in liquid nitrogen for 10 min and further placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Co 2+ -MXene composite aerogel. The mass density of the obtained aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 62.5kg / m 3 The compression strength is 2.25MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 85.4dB, and the radiation temperature of a 100℃ infrared target can be reduced to 36.1℃.
[0062] Comparative Example 1
[0063] Lightweight MXene-based electromagnetic shielding and infrared stealth aerogels, including Ti 3 C 2 T x MXene and metal ions; Ti 3 C 2 T x The size of MXene sheets is 0.1 μm; the metal ions are Co 2+ ; The Ti 3 C 2 T x MXene and Co 2+ A three-dimensional porous conductive aerogel was constructed; the freeze-drying time was 72h.
[0064] The preparation method of lightweight MXene-based electromagnetic shielding and infrared stealth aerogel comprises the following steps: adding 200-mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1 g:1 g:20 mL, and stirring at 50°C for 48 hours to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of MXene sheets is 0.1 to 2 μm; Ti with a concentration of 16 mg / mL 3 C 2 Tx The MXene aqueous dispersion was poured into the mold, and then Co with a concentration of 1.0 M was added. 2+ The aqueous solution was mechanically stirred until uniform and gelled at room temperature for 5 min to obtain Co 2+ -MXene hydrogel; Co 2+ -MXene hydrogel was frozen in liquid nitrogen for 10 min and further placed in a freeze dryer to completely dry to obtain Co 2+ -MXene aerogel. The mass density of the obtained unreinforced MXene-based electromagnetic shielding and infrared stealth aerogel is 16.3kg / m 3 The compression strength is 0.05MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 68.5dB, and the radiation temperature of a 100℃ infrared target can be reduced to 36.2℃.
[0065] Comparative Example 2
[0066] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and unmodified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene sheets is 0.1 μm; the metal ions are Co 2+ ; Aramid paper honeycomb is para-aramid paper honeycomb with a mass density of 48kg / m 3 ;Ti 3 C 2 T x MXene and Co 2+ A three-dimensional porous conductive aerogel is constructed; the unmodified para-aramid paper honeycomb is used as a mechanical property enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 72 hours.
[0067] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 200 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1g:1g:20mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of the MXene layer is 0.1 to 2 μm. The aramid paper honeycomb was ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a vacuum oven at 70 °C. Ti with a concentration of 16 mg / mL was added.3 C 2 T x The MXene aqueous dispersion was poured into the mold, and then Co with a concentration of 1.0 M was added. 2+ The aqueous solution was mechanically stirred until uniform, and the washed aramid paper honeycomb was completely immersed in it and gelled at room temperature for 5 minutes to obtain the aramid paper honeycomb reinforced Co 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Co 2 + -MXene composite hydrogel was frozen in liquid nitrogen for 10 min and further placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Co 2+ -MXene composite aerogel. The mass density of the obtained unmodified aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 62.1kg / m 3 The compression strength is 2.13MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 42.1dB, and the radiation temperature of a 100℃ infrared target can be reduced to 39.6℃.
[0068] Table 1 shows Examples 1 to 5 and Comparative Examples 1 and 2 for preparing lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogels, as well as a comparison of the mass density, compressive strength, electromagnetic shielding performance and infrared stealth performance of the prepared composite aerogels.
[0069] As can be seen from Table 1, Examples 1 to 5 are Ti crosslinked with metal ions. 3 C 2 T x MXene aerogel is a three-dimensional porous conductive network with modified aramid paper honeycomb as the mechanical performance enhancing skeleton, and a lightweight and high-strength MXene-based electromagnetic shielding and infrared stealth composite aerogel is obtained by metal ion induced gelation-freeze drying method. Comparative Example 1 is an unreinforced lightweight MXene-based electromagnetic shielding and infrared stealth aerogel, and Comparative Example 2 is a lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel reinforced with unmodified aramid paper honeycomb. Compared with the unreinforced lightweight MXene-based electromagnetic shielding and infrared stealth aerogel in Comparative Example 1 and the lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel reinforced with unmodified aramid paper honeycomb in Comparative Example 2, the lightweight and high-strength electromagnetic shielding and infrared stealth composite aerogel in Examples 1 to 5 has excellent mechanical properties, electromagnetic shielding properties and infrared stealth properties. The reason is that the introduction of aramid paper honeycomb can significantly improve the mechanical properties of MXene-based electromagnetic shielding and infrared stealth composite aerogel. In addition, after the aramid paper honeycomb is modified, it is combined with Ti 3 C 2 T x The interaction between MXene becomes stronger, overcoming the unmodified aramid paper honeycomb and Ti 3 C 2 Tx The problems of poor MXene interface bonding and gaps can be solved, thereby effectively improving the electromagnetic shielding performance and infrared stealth performance.
[0070] Table 1
[0071]
[0072]
[0073] The schematic diagram of the aramid paper honeycomb reinforced MXene-based composite aerogel obtained in Example 5 is as follows Figure 1 The obtained composite aerogel is formed by the metal ion-induced gelation of Ti 3 C 2 T x The MXene aerogel and modified aramid paper honeycomb are composed of light weight, high strength, high electromagnetic shielding efficiency and infrared stealth. The scanning electron microscope photo of the aramid paper honeycomb reinforced MXene-based composite aerogel obtained in Example 5 is shown in the figure. Figure 2 As shown in FIG. 1 , the obtained composite aerogel has a dense and uniform porous structure. The compressive stress-strain curve provided by the unreinforced MXene-based aerogel obtained in Comparative Example 1 is shown in FIG. Figure 3 Its mechanical properties are relatively low, and the compressive strength at a compressive strain of 74% is only 0.05 MPa. The compressive stress-strain curve provided by the aramid paper honeycomb reinforced MXene-based composite aerogel obtained in Example 5 is shown in Figure 4 As shown in Figure 2, the mechanical properties of MXene-based composite aerogels are significantly improved by aramid paper honeycomb reinforcement, and the compressive strength reaches 2.25 MPa.
[0074] Example 6
[0075] Lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, including Ti 3 C 2 T x MXene, metal ions and modified aramid paper honeycomb; Ti 3 C 2 T x The size of MXene sheets is 0.1 μm; the metal ions are Ca 2+ ; Aramid paper honeycomb is para-aramid paper honeycomb with a mass density of 32kg / m 3 ; The Ti 3 C 2 T x MXene and Ca 2+ A three-dimensional porous conductive aerogel is constructed; the modified para-aramid paper honeycomb is used as a mechanical performance enhancement skeleton to effectively improve the pressure-bearing performance of the composite aerogel; the freeze-drying time is 72 hours.
[0076] The preparation method of the lightweight high-strength electromagnetic shielding and infrared stealth composite aerogel comprises the following steps: adding 200 mesh MAX phase ceramic powder to a lithium fluoride / hydrochloric acid mixed solution, controlling the ratio of the three to be 1g:1g:20mL, and stirring at 50°C for 48h to obtain a black dispersion, washing, centrifuging and vibrating to obtain a dark green Ti 3 C 2 T x MXene aqueous dispersion, Ti 3 C 2 T x The size of the MXene layer is 0.1 μm; the aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a 90°C vacuum oven. The para-aramid paper honeycomb is immersed in a 10g / L NaOH solution, heated to 60°C, stirred for 2.5h, washed with deionized water and dried in a vacuum oven at 80°C. The aramid paper honeycomb is soaked in a 33wt% hydrochloric acid solution for 1min for ion exchange, washed with deionized water and dried; tris(hydroxymethyl)aminomethane is dissolved in deionized water, hydrochloric acid solution is added, the pH of the solution is adjusted to 8.5, and Tris-HCl buffer is prepared. Then, 150mg of dopamine hydrochloride is added to 150mL Tris-HCl buffer, ultrasonically treated for 5min, stirred until the solution turns pink, added to the aramid paper honeycomb, and reacted at room temperature for 5h to prepare polydopamine-modified aramid paper honeycomb; Ti with a concentration of 8mg / mL is added. 3 C 2 T x The MXene aqueous dispersion was poured into the mold, and then Ca2PO4 with a concentration of 0.6 M was added. 2+ The aqueous solution was mechanically stirred until uniform, and the modified aramid paper honeycomb was completely immersed in it, and gelled at room temperature for 5 minutes to obtain the aramid paper honeycomb reinforced Ca 2+ -MXene composite hydrogel; Aramid paper honeycomb reinforced Ca 2+ -MXene composite hydrogel was frozen in liquid nitrogen for 5 min and further placed in a freeze dryer to completely dry to obtain aramid paper honeycomb reinforced Ca 2+ -MXene composite aerogel. The mass density of the obtained aramid paper honeycomb reinforced MXene-based electromagnetic shielding and infrared stealth composite aerogel is 39.1kg / m 3 The compression strength is 1.18MPa, the electromagnetic shielding effectiveness in the X-band (8.2-12.4GHz) is 41.2dB, and the radiation temperature of a 100℃ infrared target can be reduced to 39.2℃.
Claims
1. A method for preparing a lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, characterized in that: The specific steps include: Step 1, prepare Ti3C2T x MXene aqueous dispersion; Step 2, pre-treating the aramid paper honeycomb; Step 3, preparing a polydopamine-modified aramid paper honeycomb according to the product obtained in step 2; Step 4, preparing an aramid paper honeycomb reinforced MXene-based composite hydrogel according to the products obtained in step 1 and step 3; Step 5, freezing the aramid paper honeycomb reinforced MXene-based composite hydrogel obtained in step 4 in liquid nitrogen, and completely drying it in a freeze dryer to obtain an aramid paper honeycomb reinforced MXene-based composite aerogel.
2. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 1, characterized in that: The specific process of step 1 is as follows: The MAX phase ceramic powder was added into a hydrochloric acid / lithium fluoride mixed solution and stirred at 50 °C for 48 h to obtain a black dispersion. After washing, centrifugation and oscillation peeling, a dark green Ti3C2T x MXene aqueous dispersion.
3. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 2, characterized in that: In the step 1, MXene is prepared in a mixed solution system of hydrochloric acid and lithium fluoride using 200-400 mesh MAX phase ceramics as raw materials, and the ratio of MAX phase ceramics, lithium fluoride and hydrochloric acid is 1-2 g: 1-2 g: 20-40 mL, Ti3C2T x The size of MXene flakes is 0.1 to 2 μm.
4. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 2, characterized in that: The specific process of step 2 is: The aramid paper honeycomb is ultrasonically cleaned in anhydrous ethanol and then washed with deionized water, and then dried in a vacuum oven at 50-100° C. The aramid paper honeycomb is immersed in a 5-15 g / L NaOH solution, heated and stirred, washed with deionized water, and then dried in a vacuum oven at 70-100° C. The aramid paper honeycomb is immersed in a 33wt% hydrochloric acid solution for 1-5 minutes for ion exchange, washed with deionized water, and then dried in an oven at 100-120° C. for 5-10 hours to obtain the product.
5. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 4, characterized in that: In the step 2, the aramid paper honeycomb is a para-aramid paper honeycomb or a meta-aramid paper honeycomb.
6. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 4, characterized in that: The specific process of step 3 is as follows: Dissolve tris(hydroxymethyl)aminomethane in deionized water, add hydrochloric acid solution, adjust the pH of the solution to alkaline, prepare Tris-HCl buffer, then add dopamine hydrochloride to the Tris-HCl buffer, ultrasonically treat, stir until the solution turns pink, add the aramid paper honeycomb obtained in step 2, and react at room temperature for 5 to 24 hours to obtain a polydopamine-modified aramid paper honeycomb.
7. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 4, characterized in that: The specific process of step 4 is as follows: The Ti3C2T prepared in step 1 x The MXene aqueous dispersion is poured into the mold, and then the metal ion solution is added and mechanically stirred until uniform. The modified aramid paper honeycomb is completely immersed and gelled at room temperature for 5 to 15 minutes to obtain the aramid paper honeycomb reinforced MXene-based composite hydrogel.
8. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 7, characterized in that: In step 4, Ti3C2T x The concentration of MXene aqueous dispersion is 8-16 mg / mL; In step 4, the metal ion is Co 2+ 、Ni 2+ , Cu 2+ 、Zn 2+ Mg 2+ and Ca 2+ One of; The concentration of the metal ion solution in step 4 is 0.6-1.0M.
9. The method for preparing the lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel according to claim 7, characterized in that: In step 5, the freezing time in liquid nitrogen is 5 to 10 minutes; and the freeze-drying time is 72 to 150 hours.
10. A lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel, prepared by the method for preparing a lightweight, high-strength electromagnetic shielding and infrared stealth composite aerogel as claimed in any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of light high-strength superelastic electromagnetic shielding aerogel
CN120535820A